UI/UX Design of The ENC Application as Electronic Nursing Care in Clinical Practice Education for Nursing Students in Hospitals. - Minanton, Minanton; Agustina, Habsyah Saparidah; Khoirunnisa, Nurfitria (Information Technology and Science (ITScience), 2024)
The implementation of hospital information systems in the digitalization-based era, including medical records, currently shows that there is a need for nursing education to focus on information education, including developing electronic-based practical student nursing care applications. This research aimed to design the user interface and user experience of electronic nursing documentation, named